(untitled) (Nuntius Antiquus, 2012)
Abstract: In this paper we examine Helen’s character in the Iliad by focusing on her self-characterization as a dog (ku/wn) and dogface (kunw pij). Firstly, we look at the general ethos of dogs in Homerand then we consider the meanings of dog metaphors applied toother characters throughout the Iliad and the Odyssey. By doing this,we conclude that Helen’s uses of dog-insults are paradoxically relatedto her sense of ai)dw/j.